Loans to LDCs and massive defaults - Ramesh C. Garg (Intereconomics, 1981)
The quadrupling of oil prices since the end of 1973 was accompanied by a rapid increase in the borrowings of developing countries. A global view of their external debt situation reveals some alarming realities.
Keywords: 330; Indebtedness